STRATEGI KOMUNIKASI POLITIK ANIES BASWEDAN DI TIKTOK UNTUK MENARIK PEMILIH GEN Z PADA PILPRES 2024 - Zahrah Mahfudzah Firdaus; Arfian Suryasuciramdhan; Meiby Zulfikar (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
The digital transformation has shifted political communication strategies from conventional media to new platforms such as TikTok, which is widely used by Generation Z. This shift compels political actors to adopt new communication approaches to effectively engage young voters. This study aims to analyze Anies Baswedan’s political communication strategy through live broadcasts on TikTok, using Harold D. Lasswell’s communication theory as the analytical framework. A descriptive qualitative method with a case study approach was employed, focusing on the content and interaction during TikTok live sessions. The findings show that TikTok is an effective political communication channel due to its capacity for real-time interaction, personalized messaging, and the use of visual and narrative formats that align with Gen Z's preferences. The study concludes that choosing the right digital media, particularly TikTok, is a strategic element in building engagement with young voters in the digital political era.